Diversity of Medicinal Plants Used by Traditional Healers of Dayak Desa Tribe in the Villages of Kebong and Merpak, Sintang Regency - Fathul Yusro; Resky Pranaka; Indah Budiastutik; Yeni Mariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2020)
Dayak Desa is a sub-tribe of a large group of Dayak tribes in West Kalimantan. Within the tribal community, it is estimated that there are still several traditional healers (battra) practicing traditional medicine. This study aims to identify the existence of traditional healers from the Dayak Desa tribe in the villages of Kebong and Merpak, analyze the species of medicinal plants used by traditional healers of Dayak Desa and analyze the similarities/ differences in knowledge of medicinal plants possessed by traditional healers and the general communities in Kelam Permai Sub-district. This study used an in-depth interview method to traditional healers from the Dayak Desa tribe with questionnaire aids, which contains questions related to the species of medicinal plants used in their practice. Data analysis was in the form of many species of medicinal plants used by traditional healers, plant families, habitus and parts of plants used, methods of processing and use, location, and sources of medicinal plants taken. The results showed that in Kebong and Merpak villages, there were still four traditional healers practicing traditional medication and using 59 species of medicinal plants. There are 39 species of plants used by traditional healers and also used by the communities, while 20 species others only used by traditional healers. The highest use is found in the family of Poaceae (5 species), herb habitus (37%), processing method by boiling (30%), and administration method by drinking (29%), and paste (29%), the form of single-use and mixture is quite balanced (49 and 48%). The primary source of obtaining medicinal raw materials comes from the yard (57%), and plant sources come from wild growing (59%). The knowledge of medicinal plants possessed by traditional healers should be continued documented; thus, the diversity of medicinal plants can be preserved for the next generation.